2020
DOI: 10.3389/fnagi.2020.570992
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Psoriasis and Dementia: Current Evidence

Abstract: Background: Psoriasis and dementia are both inflammatory diseases. The association between psoriasis and dementia has rarely been investigated, and the existing results are conflicting. Thus, we conducted this study to evaluate whether an association exists between psoriasis and dementia. Methods: We searched for studies from six databases from inception to July 30, 2020, using subject and free words. RevMan 5.4 was used to calculate the risk ratio (RR) of dementia in the subjects with psoriasis. When heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 38 publications
3
18
1
Order By: Relevance
“…To evaluate guilty, an item from of a validated tool on family burden has been used. 4 Answers to the statement 'I feel guilty for my child's AD' were categorised into two groups: 'certainly yes'/'probably' (1); 'certainly not'/'I don't know' (0). Clinical severity evaluated by a proxy version of the Patient-Oriented Eczema Measure (POEM) was mild in 23.5%, moderate in 59.4% and severe in 17.1% of 251 patients.…”
Section: Feelings Of Guilt In Parents Of Children With Atopic Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate guilty, an item from of a validated tool on family burden has been used. 4 Answers to the statement 'I feel guilty for my child's AD' were categorised into two groups: 'certainly yes'/'probably' (1); 'certainly not'/'I don't know' (0). Clinical severity evaluated by a proxy version of the Patient-Oriented Eczema Measure (POEM) was mild in 23.5%, moderate in 59.4% and severe in 17.1% of 251 patients.…”
Section: Feelings Of Guilt In Parents Of Children With Atopic Dermatitismentioning
confidence: 99%
“…However, there is limited information available on cognitive functioning in patients with psoriasis. [2][3][4] In this study, we prospectively enrolled patients with psoriasis for cognitive assessment and assessed potential risk factors associated with CI in these patients.…”
mentioning
confidence: 99%
“…Compared with individuals without psoriasis, those with psoriasis were more likely to develop a dementia ( 32 ), nonvascular dementia ( 32 ), vascular dementia, ( 32 ) and Parkinson's disease ( 33 ) in our study ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 60%
“…In contrast, several epidemiological studies have found a relationship between diabetes and the risk of AD [ 45 ] in the general population. Individuals with psoriasis have been reported to have an increased risk of developing dementia [ 46 ].…”
Section: Discussionmentioning
confidence: 99%